1988
DOI: 10.1039/c39880000071
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of a supported gold catalyst for acetylene hydrochlorination

Abstract: A novel high activity, carbon supported, gold catalyst for acetylene hydrochlorination which can be successfully reactivated by HCI treatment is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
134
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 0 publications
3
134
1
5
Order By: Relevance
“…These supported metal chlorides did not include gold and it was on the basis of this correlation that it was predicted that cationic gold would be the best catalyst for this reaction (22), and indeed this was subsequently confirmed (23)(24)(25). The correlation with the standard electrode potential has recently been confirmed (21) for catalysts containing 1 wt% metal (Figure 1) was short lived.…”
Section: Correlation Of Activity With the Standard Electrode Potentialmentioning
confidence: 60%
“…These supported metal chlorides did not include gold and it was on the basis of this correlation that it was predicted that cationic gold would be the best catalyst for this reaction (22), and indeed this was subsequently confirmed (23)(24)(25). The correlation with the standard electrode potential has recently been confirmed (21) for catalysts containing 1 wt% metal (Figure 1) was short lived.…”
Section: Correlation Of Activity With the Standard Electrode Potentialmentioning
confidence: 60%
“…However, in the context of oxidizing metallic Au the concentration of HCl employed here is significantly lower than in other studies, limiting the oxidation potential of the reaction environment and possibly explaining the lack of Au oxidation in the presence of HCl alone. 7,16,24 Yet this consideration does not explain why a significant increase in normalized white line height is observed under a HCl/C 2 H 2 reaction mixture but not with HCl/Ar alone.…”
Section: Acs Catalysismentioning
confidence: 90%
“…Haruta and coworkers (9,10) found that gold, when deposited as nanoparticles on a support using techniques such as deposition-precipitation and co-precipitation, was very active for CO oxidation at ambient temperature as well as at temperatures as low as -76°C. Whilst Hutchings (11)(12)(13)(14) demonstrated that supported gold chloride was the most effective catalyst for ethyne hydrochlorination.…”
Section: Introductionmentioning
confidence: 99%